The effects of alley cropping and fertilizer application on continuously cropped maize - Shannon, D.A.; Vogel, W.O.; Kabaluapa, K.N. (1994)
A trial was conducted to study the long-term effects of alley cropping on maize under continuous cropping with and without fertilizer. Maize was planted twice a year for four years. Maize yields were higher with alley cropping than without alley cropping from the fourth crop onward. Fertilizer application increased yield for each crop. Average yields over the eight crops were highest for the combination of alley cropping and fertilizer application. The long-term effects of the treatments on maize yield were estimated by regression of grain yield on time expressed as consecutive maize crops. A dummy variable was included in the multiple regression equations to account for cropping seasons in which drought or other factors severely reduced yields. Without alley cropping, maize yields declined, while with alley cropping, maize yields increased over time. Alley cropping with moderate fertilizer use may be the best means to stabilize yield and to increase productivity where long fallow periods are no longer possible.